MEMBANGUN EPISTEMOLOGI PENDIDIKAN ISLAM MELALUI KEPEMIMPINAN SPIRITUAL: SUATU TELAAH DISKURSIF - Fauzi, Ahmad (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Islamic education is currently dealing with the problems of quality and negative cycle. A number of studies have shown that leadership is a pivotal factor in the efforts to transform the negative into positive cycle, the unqualified into qualified schools; it also plays a significant role in the development of Islamic education.This article outlines the ideas and understanding of spiritual leadership and its significance in improving the quality of continuously degrading Islamic education. Through a descriptive analysis, this article argues that the stagnant educational system is partly due to the Western concept-purely based education and it offers spiritual leadership as an alternative.Keywords: Pendidikan Islam, Kepemimpinan Spiritual, Kekuatan Individu